AVALIAÇÃO DE RUÍDO EM ESCOLAS - Hans, Ramon Fernando (Revista Liberato, 2013)
“Analysis of Noise Levels at School Environment” This paper presents an analysis of noise levels at locals which are used for teaching at Fundação Escola Técnica Liberato Salzano Vieira da Cunha, in Novo Hamburgo. We can find a great number of researches showing that noise levels in schools are high due to the presence of fans, heating systems, laboratory equipment, people talking, and also the fact that the government, school directors, teachers and students are not always concerned and aware of the negative effects of noise upon human health and students output. Classrooms, courses, support and administrative rooms were chosen to be analyzed at Fundação Liberato. It is believed that noise levels higher that those established by the Brazilian law (NBR 10152) will be found. There were carried out frequency spectrum, both on environment and humans, this way allowing the analysis of the kind of noise. A parallel research was developed through a questionnaire answered by employees, teachers and students about environmental condition and acoustic. It was observed that, even in the morning, afternoon or evening, all values were higher when compared with the Brazilian Association of Technical Rules for the classrooms and laboratories [35 to 45 dB(A)], libraries [35 to 45 dB(A)], and circulation and common areas. Classrooms and laboratories show medium Leq of 71,7 dB(A), with SPLmax of 105 dB(A) and minimum of 40,5 dB(A), where we find noise sources such as voices, furniture and laboratory equipment movement and circulation of people. A medium Leq of 74,8 dB(A), with SPLmax. Of 97,1 dB(A) and SPLmin. of 49 dB(A) occur at circulation areas, bar and gymnasium – the greatest source is the noise among students. The administrative and support rooms were also measured. In these rooms, a medium Leq of 70,1 dB(A), with maximum SPL of 108,6 dB(A) and minimum of 55,7 dB(A) were found for the following noises sources: voices, air-conditioning system, telephone, and furniture movement.